Pengembangan Pengelolaan Sampah Perkotaan dengan Pola Pemanfaatan Sampah Berbasis Masyarakat - Slamet Raharjo; Taufiq Ihsan; Sri Rahmiwati Yuned (Universitas Andalas, 2016)
Bukittinggi generates around 471,01 m3/day of municipal solid waste (MSW), in which only 55,7 % is managed by the local government. As many other cities, Bukttinggi is facing a problem of implementing recycling practice. Meanwhile, there are abundant of waste from coming from districts around the border area. Such problems result in a high generation of waste that must be transfered to landfill. In order to reduce the waste generation, Bukittinggi needs a 20 years-planning of MSW development which is based on recycling management (2016-2030). It includes technical aspect and non technical aspect. The purpose of this study is to increase service coverage by developing community-based recycling facilities (TPS 3R). Developing area is divided into 3 zones. The level of service in zone 1 is increased to 100% by practicing waste reduction management in TPS 3R.. 3R target is set at 20 % of total waste generation at the end of the planning year with management system such as takakura composting, rotary klin composting and dry garbage bank. Planning with community-based waste recycling will decrease the amount of waste management facilities.Keywords: Waste Management, Bukittinggi, technical aspect, non technical aspect, 3RAbstrakKota Bukittinggi dengan timbulan sampah 471,01 m3/hari dan hanya terlayani 55,7% dari total sampah. Permasalahan persampaan yang ada di Kota ini yaitu masih rendahnya praktek pemanfaatan sampah, selain itu adanya sampah kiriman dari kabupaten tetangga yang menyebabkan jumlah timbulan sampah meningkat, sementara Kota Bukittinggi tidak memiliki TPA sendiri. Untuk itu diperlukan perencanaan pengembangan pengelolaan sampah Kota Bukittinggi selama 20 tahun perencanaan (2016-2035) meliputi aspek teknis dengan pola pemanfaatan sampah. Pengelolaan persampahan yang direncanakan yaitu meningkatkan daerah pelayanan dengan dibagi menjadi 3 zona yaitu zona I, II dan III berdasarkan kawasan strategis kota dan tingkat pelayanan menjadi 100% pada zona prioritas (Zona I) dengan melakukan reduksi sampah melalui pengolahan di TPS 3R berdasarkan target 3R, 20% di akhir tahun perencanaan dengan sistem pengolahan berupa pengomposan dengan sistem takakura susun dan rotary kiln serta bank sampah untuk sampah kering yang bisa didaur ulang. Berdasarkan analisis perbandingan, adanya pengolahan sampah dapat mengurangi jumlah sarana prasarana pengelolaan sampah.Kata kunci: Pengelolaan, Bukittinggi, Aspek Teknis dan Non Teknis, 3R